A Contemporary Insight Into the Seroepidemiology of Herpes Simplex Virus Infection in the Sub-Himalayan Region - Sangeeta Deka; Mithilesh Kumar Jha; Pratima Gupta; Putul Mahanta; Deepjyoti Kalita (The Scientific World Journal)
Infection by human herpes simplex virus type 1 and type 2 (HSV-1/2) is common globally though with wide regional variability. Seroepidemiology of HSV-1/2 infections is of utmost importance in formulating control strategies, but there is a paucity of data from many regions of India. This study aimed to determine the prevalence of anti-HSV-1/2 antibodies in Uttarakhand and adjoining areas and to study its pattern and distribution in different subgroups. Serum samples from 322 cases were subjected to ELISA test to check for the presence of anti-HSV-1/2 IgG and IgM antibodies. Sociodemographic and clinical information were extracted from medical records. The association of seropositivity and associated factors was analyzed using Fisher’s exact test. The overall HSV-1/2 seropositivity was observed to be 46.0% (95% confidence interval [CI]: 40.5–51.4). Total IgM and IgG were found in 6.2% (95% CI: 3.6–8.8) and 45.3% (95% CI: 38.1–48.9) cases, respectively. No significant difference between seropositivity of males and females was observed (45.7% in males versus 46.2% in females; p value: 0.928). Seroprevalence increased with age in both genders but was more pronounced in males (p value: <0.001), while 50.6% of women in the reproductive age group (18–30 years) were found to be seropositive. Females from Uttarakhand, compared to adjoining states (p value: 0.041) and both men and women residing in hilly terrain compared to plains (p value: 0.018; p value: 0.030), showed significantly lower prevalence, while urban-dwelling men showed higher seropositivity (p value: 0.048). Thus, HSV-1/2 seroprevalence is lower in this region, especially in young, rural, and hill dwellers, indicating majority are vulnerable to acquiring new infections. More awareness among high-risk groups and implementation of targeted public health policies can help control the disease burden.